2010
DOI: 10.1111/j.1600-0838.2009.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the polygenic profile determine the potential for becoming a world‐class athlete? Insights from the sport of rowing

Abstract: We determined whether the polygenic profile computed with seven candidate polymorphisms (i.e., ACE, ACTN3, AMPD1, CKMM, HFE, GDF-8 and PPARGC1A) for endurance performance is different in 39 world-class and 15 national-class Spanish (Caucasian) lightweight rowers. The second purpose was to examine the impact of possessing a "preferable" polygenic profile on the sport success in terms of the number of medals won in World and National Championships. Finally, we also compared the polygenic profile of world- and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 29 publications
4
39
3
3
Order By: Relevance
“…Such performance would seem to arise from the interaction between environmental factors (i.e., years of intense training stimuli) and an overall 'favourable' (though not necessarily 'optimal') genetic endowment. This is in agreement with recent findings with other Caucasian (Spanish) athletes Ruiz et al 2010;Santiago et al 2009). On the other hand, to note is that those polymorphisms for which we found greater differences between endurance athletes and controls (i.e., greater frequency of individuals with a GS of 2) were the three polymorphisms in NRF2, and PPARGC1A Gly482Ser (Table 4).…”
Section: Discussionsupporting
confidence: 94%
“…Such performance would seem to arise from the interaction between environmental factors (i.e., years of intense training stimuli) and an overall 'favourable' (though not necessarily 'optimal') genetic endowment. This is in agreement with recent findings with other Caucasian (Spanish) athletes Ruiz et al 2010;Santiago et al 2009). On the other hand, to note is that those polymorphisms for which we found greater differences between endurance athletes and controls (i.e., greater frequency of individuals with a GS of 2) were the three polymorphisms in NRF2, and PPARGC1A Gly482Ser (Table 4).…”
Section: Discussionsupporting
confidence: 94%
“…Such phenomenon would explain specific genetic differences among individuals (i.e. Olympic-class sprinters vs. Olympic-class endurance athletes) Santiago et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Using this score, it is possible to assess the balance between several selected di erent polymorphisms that are knowingly relevant to performance 41 . From 2009 to the present day, the TGS has been used by some research groups and has proved to be a sensitive tool to di erentiate endurance from strength/power athletes 31,47,[53][54] . Additionally, the use of TGS has revealed that high-elite athletes have a polygenic pro le signi cantly di erent from the general population, which probably makes athletes more favourable to sports success 18 .…”
Section: The Importance Of Making Comparisons Between Homogeneous Groupsmentioning
confidence: 99%